Comparative study of quality of life between end- stage renal disease patients treated with dialysis and those treated with kidney transplantation at King Chulalongkorn Memorial Hospital - Wichaisak, W.; Lueboonthavatchai, P.; Avihingsanon, Y. (Chulalongkorn Medical Journal, 2023)
Background : End- stage renal disease (ESRD) has become the common and important problem in public health of Thailand. At the present, there are two main medical treatments: 1) hemodialysis (HD), continuous ambulatory peritoneal dialysis (CAPD); and 2) kidney transplantation (KT). Each treatment has impact on the patient’s quality of life (QOL). Previous comparative studies about QOL of patients between the two treatment methods were inconclusive; yet there has been no study of the kind in Thailand. Objectives : To compare the QOL between that of patients with HD or CAPD and those with KT at Kidney Clinic, Department of Medicine, King Chulalongkorn Memorial Hospital. Methods : The subjects consisted of 100 HD or CAPD patients and 100 KT attending the Kidney Clinic, Department of Medicine, King Chulalongkorn Memorial Hospital during September-December 2016. The evaluation tools included, namely: 1) Demographic data form; 2) World Health Organization Quality of Life Brief – Thai, (WHOQOL-BREF-THAI); 3) Thai Hospital Anxiety and Depression Scale (Thai HADS); 4) Social Support Questionnaire; and, 5) Barthel Activity of Daily Living Index (The Barthel ADL Index). Statistics used to analyze the data were percentage, mean, standard deviation, chi-square test, independent t-test and logistic regression. Results : QOL of KT patients were higher than those of HD/CAPD in all domains and overall; especially in the psychological health domain, social relationships domain and overall.The factors associated with higher QOL in both groups of patients were higher education level, adequate economic status, illness duration above 4 years, and high levels of social support. Conclusion : QOL of KT patients were higher than those of HD/CAPD in all domains and in general; especially in the psychological health domain, social relationship domain and overall. Factors found in this study can help improve the patients’ QOL.The results of this study will be beneficial for promoting patients’ QOL.